VD_FINDINFO HC / 2009 / 176 vom 18. Mai 2009 - VD Tribunal cantonal (2009)
JUGEMENT DE DIVORCE, ACTION EN MODIFICATION, CONCUBINAGE, OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE | 129 al. 1 CC, 130 al. 2 CC, 138 al. 1 CC, 159 al. 3 CC, 119 al. 2 CPC, 374c CPC, 444 CPC, 445 CPC, 451 ch. 2 CPC, 452 al. 2 CPC, 461 CPC, 465 CPC